The Role of Public Accouting Firm Size in Moderating The Determining Factors of The Financial Statement Integrity of Public Companies in Indonesia - Malem Pagi Sembiring; Atma Hayat; Ade Adriani (Green Publisher Indonesia, 2025)
This research aims to empirically test the effect of corporate governance structure, leverage, and financial distress on the integrity of financial statements with the size of the public accounting firm as a moderating variable. The target population used is companies listed on the IDX with a total of 823 companies in 2022. The sample was selected using the purposive sampling method and obtained 491 company samples with certain criteria. This study was conducted using multiple linear regression analysis and continued with moderated regression analysis. The data in this study were processed using IBM SPSS software version 29. The results of the study indicate that partially, managerial ownership, audit committees, and leverage affect the integrity of financial statements. Meanwhile, institutional ownership, independent commissioners, and financial distress partially do not affect the integrity of financial statements. The size of the public accounting firm is able to moderate the relationship between leverage and financial distress on the integrity of financial statements. Furthermore, the size of the public accounting firm is not able to moderate the relationship between institutional ownership, managerial ownership, independent commissioners, and audit committees on the integrity of financial statements.